Storage Potential and Chemical Composition of Wet Distillers Grains with Solubles (WDGS) Treated with Different Additives - Kavitha, Patakamuri; Ravi, Arunachalam; Rao, Duddu Srinivasa; Reddy, Yeddula Ravindra; Padmaja, Kondeti; Chaitanya, Radha Krishna (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
To study the keeping quality of Wet Distillers Grains with Solubles (WDGS) during 12 days of the storage period, WDGS was treated with salt, citric acid, lactic acid, propionic acid and sulfuric acid at 1% of DM. No surface spoilage was observed up to 6 days in any of the treatments and up to 12 days in propionic and sulfuric acid treated WDGS. Mean pH was significantly lower (p<0.01) in 1% sulfuric acid treated WDGS. Mean NH3-N (mg/100g) concentration increased (p<0.01) from 0 day to 6th day and then decreased towards 12th day of storage among treatments with higher mean value in 1% sulfuric acid (100.32) and lower value in 1% propionic acid (67.26) treated WDGS. Yeast count increased towards 12th day of storage in all the treatments with higher counts in 1% salt treated WDGS. From 0 day to 12th day of storage, mean CP values were decreased significantly (p<0.01) with higher (p<0.01) mean CP value of 37.18% in propionic acid treated WDGS. Based on the overall results, it was concluded that WDGS can be stored up to 6 days without any additive, further with 1% propionic acid (DMB) treatment it can be stored up to 12 days in good quality.